Corporate technology portfolios and R&D performance measures: a study of technology intensive firms - Lin, Bou-Wen; Chen, Ja-Shen (R & D management, 2005)
This paper examines the relations between technology portfolio strategies and five commonly used research and development (R&D) performance measures. Patent and financial data of 78 US‐based technology companies from 1976 to 1995 were gathered and analysed to investigate how a well‐managed technology portfolio can create synergy and affect R&D performance. A technology portfolio can be characterized by its composition and technology concentration. A valuable technology portfolio that consists of patents with higher average citation made and self‐citation ratio can have a positive effect on firm value. Our findings suggest that large firms may enjoy advantages for technological innovation because they can exploit synergy effects of their technology portfolios. Technology concentration strategy does not work well because firms focusing on few technology fields can experience diseconomy to patents received since high‐quality patents are increasingly difficult to obtain. This paper lays the groundwork for future empirical research on technology portfolio and R&D performance.